Effectiveness of salivary glucose in diagnosing gestational diabetes mellitus - Anuradha Ganesan; Arvind Muthukrishnan; Vishnupriya Veeraraghavan (Wolters Kluwer Medknow Publications, 2021)
Context: Frequent monitoring of glucose is important in the management of diabetes. A noninvasive painless technique was used to detect glucose levels with the use of saliva as a diagnostic fluid. Aims: The aim of our study was to correlate the blood glucose levels with stimulated and unstimulated salivary samples and also to assess the reliability of using salivary glucose in diagnosing and monitoring the blood glucose levels in gestational diabetic patients. Settings and Design: The study was conducted among 100 clinically healthy nondiabetic individuals and 99 individuals suffering from gestational diabetes mellitus (GDM). Subjects and Methods: Fasting blood glucose estimation and postprandial salivary glucose estimation were done in stimulated and unstimulated salivary samples using glucose oxidase/peroxidase method. Statistical Analysis Used: Data obtained were subjected to normality test, and P ≤ 0.05 was considered to be statistically significant. The correlation between blood and salivary glucose levels was evaluated using Pearson's correlation test. Results: A positive correlation was obtained for stimulated and unstimulated salivary samples in fasting and postprandial conditions. Linear regression analysis and receiver operating characteristic curve were plotted, and the optimal cutoff value for unstimulated and stimulated salivary glucose under fasting conditions was 5.1 mg/dl and 5.4 mg/dl, respectively. The optimal cutoff value for unstimulated and stimulated salivary glucose was 8.8 mg/dl and 9.3 mg/dl, respectively, in postprandial conditions. Conclusions: Saliva appears to be a reliable biofluid to assess the blood glucose levels and can definitely be a reliable alternative to blood glucose in GDM patients.